Developing Healthy Environment for Young Mothers in Suburb Indonesia - Sari Viciawati Machdum; Fardhan Zaka Ramzy; Anna Amalyah Agus; Annisah Annisah (Asian Social Work Journal, 2019)
This article explores community services approach that intends to change the behavior of young mothers at home in serving food for their families. Research results showed that there were challenges in this suburb area., especially for young mother who can get many facilities to get their daily meals. Unfortunately, the facilities could give negative impacts on them in gaining proper nutrition. The obstacles came from many aspects of society. Thereupon, social intervention for them needs to be handled carefully so that the beneficiaries could get sustainable change. Others have argued that participation is crucial elements in community intervention. This research showed that participation its self is the hard aspect in the suburb especially at the region that has rapid development but lack of social investments. People used to get many projects from different organizations. The helping projects often did not consider sustainability matters. This condition reshapes the people. They become the object of social programs. Maintaining intensive programs based on some practices: collaboration planning and implementation could increase the trust of the beneficiaries. Based on our study on ten young women and other fourteen participants in a suburb of Indonesia, trust is primary material in changing people’s behavior. Especially educating people to live in healthy lifestyle as a vital aspect of developing a healthy environment.